LISTENING DIFFICULTIES FACED BY THE FIRST SEMESTER STUDENTS AT BASIC LISTENING CLASS - Yahmun Yahmun; Endang Sumarti; Debby Setyowati (Journey: Journal of English Language and Pedagogy, 2020)
This study aimed at describing difficulties faced by students in learning Listening. This study involved seventeen female students and eight male students taking Basic Listening course in one of private university in Malang, East Java. To gain the data, the researcher interviewed the subjects one by one. The findings, then, classified into several classes by referring to previous studies discussing listening difficulties in English as Foreign Language (EFL) classes. The findings showed that there were four difficulties faced by the students. They were the speed and length of the spoken text, vocabulary, pronunciation, and accents. Based on the findings, then, the researchers made several suggestions for further researchers and other language teachers to consider this study in their practice.